Police body-worn camera policies as democratic deficits?: comparing public support for policy alternatives - Bromberg, Daniel E. (Criminology & public policy, 2022)
Research Summary Policies that govern the use of body-worn cameras (BWCs) by police vary widely between American cities. However, it is currently unclear whether citizen preferences for these policies vary in a similar manner. More specifically, do BWC policies reflect citizen preferences or are existing policies disfavored by a majority of the public? To investigate these questions, we randomly sampled 1000 respondents for each of the three representative metropolitan areas, Los Angeles, CA; Seattle, WA; and Charlotte, NC, in addition to a further 1000 Americans across the country to inquire about policy preferences. We found that most respondents prefer the BWC policies recommended by the American Civil Liberties Union (ACLU) to those currently implemented in their regional police departments. In other words, elements of the BWC policies in Los Angeles, Seattle, and Charlotte do not reflect residents’ preferences. Policy Implications The policy stating that footage access should be given to parents of minors, a deceased subject's family members, or anyone filmed in an encounter, a model promoted by ACLU, is a clear favorite in the United States at large, but also in the three cities we studied. The policy stating that footage access should not be given to superior officers to find disciplinary infractions, also backed by the ACLU, is less popular among Americans at large and residents of Seattle. Beyond the high support for BWCs within the American population, decision makers need to make sure that the policies that govern the use of this tool respect democratic principles. Therefore, the voice of citizens needs to be heard to avoid a democratic deficit.